Determinantes da vacinação entre trabalhadores do setor saúde da Bahia - Souza, Fernanda de Oliveira (2015)
Brazil has for forty years with the national immunization program, which provides free vaccinations for the population in all cycles of life. Among the adult population, we highlight the vaccination in you work in the health sector, which have increased risk of getting sick from infectious diseases, within the work, but also outside of it. The aim of this study was to determine the vaccination status of health workers as well as the factors that determine the complete vaccination for adult calendar health ministry. for this, it was built four articles: 1 - vaccination profile of workers in the health sector of Bahia; 2 - Factors associated with vaccination among workers of primary care and medium complexity in Bahia; 3 Immunization status against hepatitis B workers of primary care and medium complexity of Bahia, Brazil; 4 - Vaccination against hepatitis B and Anti-HBs among health workers. It is considered the study of the determination of vaccination among specific groups such as health workers, a chance to build service strategies to maintain its protected population of diseases that have specific immunizations. This study sought to simplify a complex outcome. This was a pioneering study, to investigate the vaccination status and its completeness for all vaccines provided by the health ministry for adults through a methodology that could provide subsidies for triggering preventive actions to SUS workers not only to local reality, but above all national. This study allowed the analysis of information from various realities of working conditions in Bahia related to the vaccination process. Research like this certify that the knowledge produced can be used in public administration. Given the situation of low immunization when investigated the completion of the immunization schedule adults, suggest the workshops with workers linked to the health sector, focused on reducing barriers to access to vaccination strategies to improve the acceptance of immunizations and the perception of the subjects regarding their health.